QAnon : from conspiracy theory to new religious movement - Argentino, Marc-André (Routledge studies in fascism and the far right., 2026)
This book explores the QAnon movement by examining its history, fluctuations, and evolution, stemming from the likelihood of multiple users behind the "Q" account, as well as from the changes in the sociopolitical landscape since the creation of the movement. It frames QAnon as a lived religion and demonstrates that it has gone through three stages of existence: proto-QAnon, canonical-QAnon, and apocryphal-QAnon.Author Marc-André Argentino argues that QAnon evolved into something more than a conspiracy theory and demonstrates through a comparative analysis that QAnon is more akin to a new religious movement, in particular a hyper-real religion. He explores the role of gender and women in the QAnon movement, followed by an examination of how the QAnon conspiracy theories have legitimized and coordinated targeted gender-based violence. The book provides evidence of the nexus of QAnon and ideologically-motivated violent extremism and criminality. Finally, it examines the evolution of QAnon after the January 6th insurrection, the loss of the 2020 election by Donald Trump, and the disappearance of "Q." This volume will be of great interest to researchers of conspiracy theories, new religious movements, American politics, and extremism.